Research Relating to Children. Bulletin 42 September 1978-February 1979 - O'Connell, Dorothy, Comp.; ERIC Clearinghouse on Elementary and Early Childhood Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
This bulletin, number 42, provides an inventory of abstracts of ongoing or recently completed research studies relating to children. Bibliographic sources of the bulletin include ERIC documents, journal articles, books, reports, and conference papers. Citations are entered under the following categories: long-term research, growth and development, special groups of children, the child and the family, socioeconomic and cultural factors, educational factors and services, social services, and health services. Only research reported between September 1978 and February 1979 is included in this issue of the Bulletin. (Author/RH)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, DC 20402 (Stock No. 017-090-00048-8, $5.00).
Sponsoring Agency: Administration for Children, Youth, and Families (DHEW), Washington, DC.
Sponsoring Agency: Children's Bureau (DHEW), Washington, DC.
Contract Number: OCD-CB-02.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescents; Annotated Bibliographies; Child Abuse; Child Development; Child Rearing; Children; Cultural Influences; Delinquency; Educational Research; Exceptional Child Research; Family Relationship; Health Services; Infant Behavior; Longitudinal Studies; Research Methodology; Social Services; Socioeconomic Influences; Reports, Research; Reference Materials, Bibliographies